Analisis Yuridis Sertipikat Hak Atas Tanah Sebagai Alat Pembuktian di Pengadilan pada Sengketa Hak Milik Atas Tanah: Studi Terhadap Putusan No. 08/Pdt.G/2015/PN.CBN - Solikhin, -; Kusbiantoro, -; Saiman, Ridwan (E-Journal Widya Yustisia, 2020)
Soil is one of the natural resources which is very important for human life. Ownership of land is proven by cerificate. A certificate is a copy of the Land Book and Measure Letter from the Land Book data and the Measure Letter in the Land Office. It is affirmed in Article 19 paragraph (2) letter c of the UUPA (Basic Agrarian Law), a certificate of land rights is strong evidence. It means that as long as it cannot be proven otherwise, the physical data and juridical data contained in the certificate are considered as data. which is true in everyday life and before the COurt. The purpose of this study is to determine the juridical strength of the certificate of ownership rights to land as evidence in disputes over land rights at the Cirebon District Court, to determine the position of the certificate of ownership rights over land in the National Land Law and to juridically analyze the judge's judgement whether it is in accordance with the applicable legal provisions in deciding disputes over land title certificates in the form of title certificates. The method used in this research is normative juridical, data obtained from the results of library research in the form of primary legal materials, namely legislation, secondari legal materials from scientific books written by experts and tertiary materials from dictionaries and writings. It can be concluded that, according to the land registration system which is adhered to by the UUPA, it is still necessary to prove in the District Court that the Certificate of Ownership on Land in dispute is incorrect.